Utilization of Online Media and Information Sources in Online Lectures during the Covid-19 Pandemic - Antiwi, Rindi; Nasution, Muhammad Irwan Padli (Jurnal Mercusuar, 2021)
The policy of online learning during the Covid-19 pandemic is the best option considering the spread of Covid-19 that may occur if face-to-face lectures are still held. Therefore, the utilization of online media and information sources in the online learning process is mandatory for students and lecturers. To support the online learning process, media is needed as a means of communication between students and lecturers, as well as between students. Various sources of information are also available online and can be utilized by students as reference materials to understand lecture materials and for making assignments.